THE RELATIONSHIP BETWEEN THE PROCESS OF REGULATION OF LEGISLATION PROCEDURE IN LITHUANIA AND LEGISLATION EFFICIENCY - Bakševičienė, Rūta (Teisė, 2017)
There is a large number of scientific articles, where relationship between the form and content of the judicial practice are analysing. But, when the issue consists the legislation procedure, mostly scientific analysing is focused on a legal technique or on the specific problem in the particular branch of law or particular legal act. The regulation procedure in an area of a State power and relationship with a general efficiency on the beneficiary on the good of society, law system and the trust of Law is dealt with in this article. The State power or Government in this article has a broad meaning, which includes the Government of Lithuania, as a State body with a Constitutional right of legislative initiative and all large number of ministries, departments and other governmental institutions as well as working groups, appointed by the Government of Lithuania, legal and state staff. A lot of stages and norms, dedicated to the legislation procedure in this area. Each institution has it’s “own” legal act, which regulates functions and sphere of responsibility of this institution in the legislation procedure. In addition, there is a general Law of Government of Lithuania, where all ministries and main functions of competence and procedures are described. In the text of this law, one can find the legal norm, which directs to another legal act – the Regulation of the Work of the Government. In this act every stage and step of move and behaviour of each particular department is described in detail. What is specific, – the existence of legal norm in this Regulation, which describes the institutional behaviour when having disagreement between them. The norm has a name “Coordination of disagreements”. In the 2001, it changed the other legal norm, the content of which was only about agreements and conclusions, not about disagreements. Since then the number of legal norms, related with coordination and with a word “coordination” increased. The increased number of using the word “coordination” relates not only with the regulation of the legal procedure and relationships between Lithuanian institutions, but also describes the possibility for interpretation of one’s social role in social group and it is not always is in relation with efficiency of legal acts. There is no any regulation or statistics, about a general score of debates and observations, which are considering and putting in to the legal text. Mostly, it is a discretion of a particular office employee and depends only on his/her. So, it is a sphere for social role (subject), a sphere, in which someone can be satisfied only with possibility to “play his role”. So, it is also a sphere for “regulation for regulation”, for form’s domination against the content. It is obvious from the statistics that the number of legal acts and law drafts not decreases. So, a decrease of regulation norms in a procedure of legislation can increase a quality and efficiency of it: one in his social role should have more general, not specific knowledge and it also means that one must have a more open minded thinking, general values, including respect for general principals in law.